Amygdala and fusiform gyrus temporal dynamics: Responses to negative facial expressions. - Britton, Jennifer C.; Shin, Lisa M.; Barrett, Lisa Feldman.; Rauch, Scott L.; Wright, Christopher I. (2016)
Background: The amygdala habituates in response to repeated human facial expressions; however, it is unclear whether this brain region habituates to schematic faces (i.e., simple line drawings or caricatures of faces). Using an fMRI block design, 16 healthy participants passively viewed repeated presentations of schematic and human neutral and negative facial expressions. Percent signal changes within anatomic regions-of-interest (amygdala and fusiform gyrus) were calculated to examine the temporal dynamics of neural response and any response differences based on face type.; Springer Open.